Selective medium for primary isolation of members of the tribe Proteeae - Urbanová, E (Folia microbiologica, 1999)
A selective Proteeae medium (SPM) for isolation and preliminary detection of species of genera Proteus, Morganella, and Providencia was evaluated. The SPM contains tryptose phosphate agar with phenolphthalein monophosphate (as substrate for phosphatase activity), bile salts and polymyxin B (as inhibitors). The selectivity of the SPM was tested by the ecometric method of quality assurance of culture media. Fourteen reference cultures of enterobacteria and fifty-four strains of Proteeae were tested for their absolute growth index (AGI). Ninety-five percent of tested Proteeae strains display an AGI above 2.5. The detected phosphatase activity proved to be able to discriminate colonies of members of the tribe Proteeae. The ability of SPM for primary isolation of members of Proteeae was tested on food and clinical material and 94 strains were isolated. In addition, the SPM was employed in routine practice of clinical microbiology. From 1016 clinical samples (stool, urine, vaginal and urethral swabs), 57 strains of Proteeae were detected by the SPM in contrast to 35 strains by the routine procedure. The difference amounts to nearly 40%.
Keywords: druhová specificita; Culture Media; Male; Bacterial Infections; Providencia; infekce spojené se zdravotní péčí; kultivační média; Proteobacteria; mužské pohlaví; Species Specificity; potravinářská mikrobiologie; Proteus; bakteriální infekce; lidé; ženské pohlaví; Cross Infection; Food Microbiology; Humans; Morganella; Female